(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The purpose of the study was to determine the diagnostic accuracy of ultrasonography in predicting Endotracheal Tube Size in pediatric patients and to compare it with physical indices based formula. Objective: To determine the diagnostic accuracy of ultrasonography in predicting endotracheal tube size in pediatric patients.Methodology: 201 patients posted for surgeries under general anesthesia in Department of Anesthesia, Government Medical College, Thiruvananthapuram, who have given informed written consent were the source of data after obtaining the Institutional Ethics Committee clearance. Results were recorded using a preset proforma. Result: 189 (94%) of our 201 patients were intubated on the first attempt. 12 (6%) patients changed tube size with USG. Comparing USG-calculated endotracheal tube size to real size, 189 (94%) patients utilised the same size tube, 8 (4%) used a smaller size, and 4 (2%) used a larger size. Comparing ETT size using age-based formula with actual tube size, 152 (75.6%) patients used the same size tube, 6 (3%) used a smaller tube, and 43 (21.4%) used a larger tube. USG estimates ETT size at 5.51 with a standard deviation of 0.78, while age-based formula estimates at 5.66 with 0.89. The mean difference of ETT size calculated by USG and age-based formula was -0.157 with standard deviation of 0.349, paired t value 6.372, and p value <0.001. Conclusion: This study found that 94 %of children in our study had their tube size correctly predicted by ultrasound. When deciding on an endotracheal tube size for a child, ultrasonography is preferable to using age-based formulae. In children, USG is reliable for determining the best Endotracheal Tube size.